Educating Latinx and African American Students in Charter Schools: A Comparative Study from Chicago. Issue 7 (September 2022) - Bu, Qingyu; Mendenhall, Ruby
The public school system in U.S. has changed dramatically over the past few decades. Institutionally, neo-liberal reform has created a new educational apparatus known as charter schools. As they admit students without school boundaries, these schools promise to offer great opportunities for disadvantaged students. The enrollment in charter schools is mainly Latinx and Black students, especially in large urban areas. That demographic shift is not reflected in the literature because previous studies have predominately focused on comparisons between Whites and minorities. Using Chicago as a case, this study compares the association between the enrollment of Black and Latinx students with educational resources and academic performance in charter schools. Using Illinois Report Card data representing 119 public schools during the 2016 to 2017 academic year, we aimed to understand which group could more systemically benefit from charter schools. We found that although the enrollment of Black students might be associated with better educational resources (i.e., total number of school days per academic year, and class size), the enrollment of Latinx students predicted stronger school academic performance on the SAT and PARCC. Those findings can contribute to the debate about institutionalized racial inequality in education and the effects of charter schools.